Overexpression of 5‐lipoxygenase and its relation with cell proliferation and angiogenesis in 7, 12‐dimethylbenz(α)anthracene‐induced rat mammary carcinogenesis1. Issue 5 (28th December 2011) - Chatterjee, Mary; Das, Subhadeep; Roy, Kaushik; Chatterjee, Malay
Abstract The present study was performed to investigate the critical role of 5‐lipoxygenase (5‐LOX) in 7, 12‐dimethylbenz(α)anthracene (DMBA)‐induced rat mammary inflammation associated carcinogenesis. Female Sprague–Dawley rats at 50 days of age were treated with 7, 12‐dimethylbenz(α)anthracene (DMBA; 0.5 mg/100 g body weight) by a single tail vein injection, followed by administration of zileuton (2000 mg/kg diet) from week 7 until the termination of the study at 31 wk. 5‐LOX protein expression, 5‐hydroxyeicosatetraenoic acid (5‐HETE), and leukotriene B4 (LTB4) production in rat mammary tissue were analyzed at 6, 12, and 24 wk post‐DMBA injection. Rate of cell proliferation was analyzed by bromodioxyuridine labeling index (BrdU‐LI). Microvessel density, level of VEGF, and MMP‐2 were also measured. DMBA induces inflammation in rat mammary gland as early as 6 wk. 5‐LOX is upregulated in DMBA treated rats right from 6 wk when compared with their normal counterparts. An overexpression of 5‐LOX is accompanied with increase in 5‐HETE, LTB4 production and high BrdU‐LI with an increase of two key angiogenic factors for tumorigenesis; MMP‐2 and VEGF. It was found that 5‐LOX specific inhibitor brought about substantial protection against DMBA‐induced mammary carcinogenesis. Histological findings showed substantial repair of hyperplastic lesions. There was a significant reduction in the rate of cell proliferation and expression of angiogenic factors, MMP‐2 and VEGF. 5‐LOX plays an important role in DMBA‐induced inflammation associated carcinogenesis via activation of MMP‐2 and VEGF. 5‐LOX expression can be considered as a critical event in controlling the process of mammary tumor development. © 2011 Wiley Periodicals, Inc.